The Effect Of Providing Rolling Massage To Public Mothers On Breast Milk Explosion At PMB Ruri Cisauk In 2023 - Sri Rahayu, Yuliana; Rismayanti, Tetin (CV. Inara, 2024)
Background The prevalence of successful breastfeeding coverage for postpartum mothers is still very low, namely 51% of 78 mothers during 2023 and in 2022 as many as 48% of 109 mothers, from the results of interviews many mothers complained that breast milk was not coming out, babies did not want to breastfeed and other. Based on researchers' observations, many postpartum mothers give formula milk on the grounds that breast milk does not come out or there is little breast milk. The purpose of the study was to study the effect of rolling back massage on breast milk expenditure in puerperal mothers at PMB Cisauk in 2023. This research method is a Quasy Experiment, one group pre-post design, the population in this study is all postpartum mothers who were at PMB Cisauk on 29 October-25 November 2023, totaling 20 people using total samplingwith a sample size of 20 respondents, using data namely primary data with observation, analysis using the T-Dependent Test. Research results: From the statistical test results of the dependent t test, it is known that there is an effect of rolling back massage on breast milk production in postpartum mothers in PMB Cisauk in 2023 with a value of P=0.000. Conclusions and Suggestions: it is hoped that health workers can provide additional information and socialize or provide counseling when carrying out postpartum visits to families and husbands about the benefits of rolling massage to the community, especially breastfeeding mothers, to increase their breast milk output so that later mothers can breastfeed exclusively.